IMPACT OF CLOPROSTENOL SODIUM TREATMENT DURING EARLY POST PARTUM PERIOD ON FERTILITY IN DAIRY CATTLE - RAUT, M R; INGAWALE, M V; DESHMUKH, S G; HAJARE, S W; INGOLE, R S (The Indian Journal of Animal Reproduction, 2016)
Normally calved dairy cattle (n=8 in treatment and control group each) were evaluated for the impact of early post partum treatment (day 0, 5 and 10 post partum) with prostaglandin F2á analogue, cloprostenol sodium, on expulsion of placenta, uterine involution, exhibition of first post partum estrus and first service conception rate. Cloprostenol treated cattle had early expulsion of placenta and uterine involution (p<0.05), however, the outcome of remaining parameters was similar (p>0.05), thus, suggesting the beneficial impact of treatment to a certain extent in dairy cattle